309 Community Parenting and the Concept of Child Abuse in Yoruba Culture - Omobola, Odejobi Cecilia (Richtmann Publishing, 2012)
The study investigated whether or not child abuse existed in the traditional Yoruba culture. The population consistedof all the secondary students and their parents in Ile-Ife metropolis. Purposive random techniques was employed in selecting 241male and 259 female that made up of three sets of people (non-literate parents, literate parents and students) which comprisesof 66 males and 84 females non-literate parents and 75 males and 75 females literate parents as well as 100 males and 100females students that were selected from 10 secondary schools in Ile-Ife .using purposive sampling technique. A questionnairetitled â€œParenting and Child Abuse Questionnaireâ€ (PCAQ) was developed by the investigator to elicit information from bothstudents and parents on the issue related to child abuse. The non-literate parents that could not read the questionnaire weremade to respond as the investigator read in native language. The questionnaire was validated before use and the reliabilitycoefficient yielded 0.85 which is significant at 0.05 level of significance. Data were analysed statistically using percentages.Findings showed students do not see the type of training giving to them in the traditional setting as child abuse. Non-literateparents do not see fostering children as child abuse. Also the literate parents see child abuse as a fruit of western civilization.The paper concluded that child abuse should be examined within the context of culture. Practices with cultural undertonesshould not be condemned.